Complete Epstein-Barr virus seropositivity in a large cohort of patients with early multiple sclerosis - Abrahamyan, Sargis; Eberspächer, Bettina; Hoshi, Muna-Miriam; Aly, Lilian; Luessi, Felix; Groppa, Sergiu; Klotz, Luisa; Meuth, Sven G.; Schroeder, Christoph; Grüter, Thomas; Tackenberg, Björn; Paul, Friedemann; et al. (Journal of neurology, neurosurgery, and psychiatry, 2020)
Objective To determine the prevalence of antibodies to Epstein-Barr virus (EBV) in a large cohort of patients with early multiple sclerosis (MS). Methods Serum samples were collected from 901 patients with a clinically isolated syndrome (CIS) or early relapsing-remitting multiple sclerosis (RRMS) participating in the German National MS cohort, a prospective cohort of patients with early MS with stringent inclusion criteria. Epstein-Barr nuclear antigen (EBNA)-1 and viral capsid antigen (VCA) antibodies were measured in diluted sera by chemiluminescence immunoassays (CLIAs). Sera of EBNA-1 and VCA antibody-negative patients were retested undiluted by an EBV IgG immunoblot. For comparison, we retrospectively analysed the EBV seroprevalence across different age cohorts, ranging from 0 to >80 years, in a large hospital population (N=16 163) from Berlin/Northern Germany. Results EBNA-1 antibodies were detected by CLIA in 839 of 901 patients with CIS/RRMS. Of the 62 patients without EBNA-1 antibodies, 45 had antibodies to VCA as detected by CLIA. In all of the remaining 17 patients, antibodies to EBV were detected by immunoblot. Altogether, 901 of 901 (100%) patients with CIS/RRMS were EBV-seropositive. EBV seropositivity increased with age in the hospital population but did not reach 100% in any of the investigated age cohorts. Conclusion The complete EBV seropositivity in this large cohort of patients with early MS strengthens the evidence for a role of EBV in MS. It also suggests that a negative EBV serology in patients with suspected inflammatory central nervous system disease should alert clinicians to consider diagnoses other than MS.
Gesehen am 13.10.2020